2015
DOI: 10.21000/jasmr15020001
|View full text |Cite
|
Sign up to set email alerts
|

Bird Species’ Reponses to Post Mine Reclamation in Alabama – A Preliminary Analysis

Abstract: Surface mining transforms landscapes and ecosystem functions through the removal of vegetation and soil. Losses of vegetation correlate with declines, displacement, and transformations of songbird communities. Mine reclamation is a legislative requirement that can influence wildlife communities. The purpose of this study was to examine the avian community responses to mine reclamation practices and, as a proxy, assess the potential benefits and limitations of current reclamation approaches. Avian point counts … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 28 publications
(35 reference statements)
1
6
0
Order By: Relevance
“…Studies have reported grassland birds using these areas 20 years after mine reclamation (DeVault et al 2002, Ingold and Dooley 2013, Borthwick and Wang 2015, Wood and Ammer 2015, and this was evident in our study, where grassland species were present 19 years after mine reclamation. Despite reclaimed mines providing long-term habitat for grassland birds, quality can decline over time leading to reduced nesting productivity (Wood and Ammer 2015).…”
Section: Discussionsupporting
confidence: 77%
“…Studies have reported grassland birds using these areas 20 years after mine reclamation (DeVault et al 2002, Ingold and Dooley 2013, Borthwick and Wang 2015, Wood and Ammer 2015, and this was evident in our study, where grassland species were present 19 years after mine reclamation. Despite reclaimed mines providing long-term habitat for grassland birds, quality can decline over time leading to reduced nesting productivity (Wood and Ammer 2015).…”
Section: Discussionsupporting
confidence: 77%
“…The seeds result natural regeneration on mine reclamation land. In accordance with the bird diversity, vegetation diversity on mine reclamation area is the key because monoculture leads to low diversity bird species (Borthwick & Wang 2015).…”
Section: Avifaunamentioning
confidence: 99%
“…On the one hand, the processes of vegetation cover succession depend on the diversity of birds in the environment (Borthwick & Wang, 2015). On the other hand, phytocenoses and their successions determine nesting ornithocenoses: abundance and species composition (Slankard et al, 2018;Koshelev et al, 2020a).…”
Section: Introductionmentioning
confidence: 99%